2009 IEEE Conference on Electrical Insulation and Dielectric Phenomena 2009
DOI: 10.1109/ceidp.2009.5377827
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric barrier discharges in multi-layer polymer ferroelectrets

Abstract: Cellular polymer foams with bipolar internal space charge are known as ferro-and piezoelectrets. Light emission from the internal voids of such polymer foams during electrical charging was already reported a few years ago and allows the investigation of the underlying dielectric barrier discharges. More recently, polymeric layer structures with well-defined voids were presented as an alternative to polymer-foam ferroelectrets. The simpler and more uniform voids in layered ferroelectrets are more suitable as mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
3
0
2
Order By: Relevance
“…harvesting, and actuations, which are among the key procedures of various conditions such as industrial systems and bio-mimic robotics [1][2][3]. Among various electromechanical coupling effects and mechanisms, electromagnet, triboelectricity, electret, piezoelectricity and flexoelectricity contribute on different conditions due to their advantages and restrictions [1][2][3][4][5][6][7][8]. Among these effects and materials, stretchable electrets are expected as energy converting-active materials because they 'hold' net charges quasi-permanently, and hence output high electromechanical coupling efficiencies [9] with ultra-high deformation range.…”
Section: Introductionmentioning
confidence: 99%
“…harvesting, and actuations, which are among the key procedures of various conditions such as industrial systems and bio-mimic robotics [1][2][3]. Among various electromechanical coupling effects and mechanisms, electromagnet, triboelectricity, electret, piezoelectricity and flexoelectricity contribute on different conditions due to their advantages and restrictions [1][2][3][4][5][6][7][8]. Among these effects and materials, stretchable electrets are expected as energy converting-active materials because they 'hold' net charges quasi-permanently, and hence output high electromechanical coupling efficiencies [9] with ultra-high deformation range.…”
Section: Introductionmentioning
confidence: 99%
“…The voids of latter structures possess charges of opposite sign trapped at opposing inner air/polymer interfaces which can be regarded as oriented micrometer-size dipoles. When subjected to mechanical or electrical stimulation, the dipole moments of such structures change strongly due to the soft air-filled phase in an otherwise cellular polymer framework [10][11][12] which can be 'engineered' by processing [13][14][15] or assembling of suitable polymer materials [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The voids with the lowest critical field determine the critical field of the film (minimum field needed for the film to become electromechanically active). When the applied field is larger than this minimum, the charge density of the film (and as a result its piezoelectric coefficient d 33 ) increases linearly with the field [3] up to an equilibrium field where no more charges can be forced inside the material [4,5]. It has been shown that the equilibrium field is about two times the critical field of the film [4].…”
Section: Introductionmentioning
confidence: 99%